SANCTIONS ON INDISCIPLINARY EMPLOYEES IN THE PERSPECTIVE OF FIQH MUAMALAH: A STUDY ON THE ACEH CIVIL SERVICE AGENCY - Sausan Athirah; Azka Amalia Jihad; Muhammad Rasyid, Laila (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This research examines the process of proving an ijārah 'ala al-'amāl contract and the effectiveness of sanctions applied by the Badan Kepegawaian Aceh. The method used is an empirical legal approach in which data is collected from primary sources such as interviews, observations, and focus group discussions. Secondary data is collected from secondary sources such as books, journals, and other resources related to this research. The findings show that the sanctions applied have not been fully effective in tackling arrears. This research is important because the sanction policy of Badan Kepegawaian Aceh needs to be evaluated in order to improve the supervision and enforcement of employee discipline, as well as to ensure that the application of ijārah 'ala al-'amāl is in accordance with applicable principles. The level and type of sanctions for default are listed in Government Regulation No. 94 of 2021 on the Discipline of Civil Servants. Meanwhile, defaulting employees are subject to a series of disciplinary enforcement procedures. The first step is a warning in the form of a summons to provide information about the absence. If the employee fails to comply with the summons, a follow-up summons will be issued. If the employee still refuses to comply, disciplinary action will be taken. The first disciplinary action will usually be a light sanction. This serves as a warning and encouragement to comply with attendance and work discipline rules. However, if the employee still repeats the offence or commits another offence, moderate or more severe sanctions will be imposed. These include sanctions such as deduction of TTP, demotion, delayed salary increases, or even dismissal, depending on the policy and the level of offence committed.